GDPR personal data protection in the European Union - Krzysztofek, Mariusz (European monographs, 2021)
"Personal data protection has become one of the central issues in any understanding of the current world system. In this connection, the European Union (EU) has created the most sophisticated regime currently in force with the General Data Protection Regulation (GDPR) (EU) 2016/679. Following the GDPR's recent reform - the most extensive since the first EU laws in this area were adopted and implemented into the legal orders of the Member States - this book offers a comprehensive discussion of all principles of personal data processing, obligations of data controllers, and rights of data subjects, providing a thorough, up-to-date account of the legal and practical aspects of personal data protection in the EU. Coverage includes the recent Court of Justice of the European Union (CJEU) judgment on data transfers and new or updated data protection authorities' guidelines in the EU Member States"--